Unveiling the Efficiency of Biodegradable Chitosan-Based Hydrogel Composites for Wastewater Treatment - Iulia Elena Neblea; Anita-Laura Chiriac; Anamaria Zaharia; Tanța-Verona Iordache; Ana-Mihaela Gavrilă; Andreea Miron; Sorin-Viorel Dolana; Ana-Lorena Neagu; Andreea Olaru; Mircea Teodorescu (Proceedings, 2023)
This work presents the efficiency of interpenetrated chitosan-based hydrogels (IPNs) in the treatment of WW in a laboratory micro-pilot device which allowed both the use of a larger volume of compounds and an improved stirring of the samples throughout the test period.